KESALAHAN PENGGUNAAN EJAAN BAHASA INDONESIA PADA BROSUR PENERIMAAN PESERTA DIDIK BARU JENJANG SMA DI KABUPATEN SINTANG - Yusi Kurniati (Jurnal Bahasa Indonesia Prima (JBIP), 2023)
This study discusses the language errors in the brochure for New Student Admissions for the Sintang District High School level. The errors studied included errors in capital letters, italics, punctuation, diction, and prepositions. This research data is 6 brochures for New Student Admission to the high school level in Sintang Regency. This research is qualitative research with a descriptive method. Data analysis stages are carried out by collecting data, identifying, classifying, and evaluating errors. The basis used to analyze the data is PUEBI. Of the six brochures, the SMKN 1 Kelam Permai brochure found the most errors. Meanwhile, the fewest errors were found in the SMAN 1 Binjai Hulu brochure.